A Technique to Reduce the Early Recurrence of Intussusception in Ultrasound‐Guided Hydrostatic Reduction. (25th December 2021) - Yu, Feng; Chen, Huanhua; Cao, Xiaoqing; Mao, Weihao; Jiang, Shuanglan; Yao, Zhiguang; Zhang, Min
Abstract : Objectives: Ultrasound‐guided saline enema is highly successful in treating pediatric intussusception; however, early recurrence—within 48 hours—is possible. This study aimed to explore effective methods of reducing early recurrence. Methods: This study included patients aged 0 to 14 years diagnosed with ileocolic intussusception with a symptom duration of <48 hours from January 2019 to March 2021. The patients were divided into control and intervention groups. All patients received successful treatment with ultrasound‐guided saline enema; however, in patients treated before January 4, 2020 (control group), the intestinal fluid was drained immediately, and in patients treated after January 4, 2020 (intervention group), the intestinal fluid was drained after 15 minutes of intestinal pressure maintenance. Early recurrence rates of the groups were compared. Results: Ileocolic intussusception was treated successfully by ultrasound‐guided saline enema in 231 patients (116, control group;115, intervention group). The early recurrence rate in the intervention group (10%; 95% CI: 4.9–16.5) was numerically lower than that in the control group (19%; 95% CI: 12.3–27.3). No significant difference was observed in the number of recurrences per person between the groups ( P = .448). Patients without early recurrence were older ( P = .004) and received enemas of a shorter duration ( P < .001) and lower pressure ( P < .001) than patients without early recurrence. Conclusions: Maintaining reduction pressure for 15 minutes after a successful ultrasound‐guided saline enema may reduce the early recurrence of intussusception. A randomized controlled trial is needed because the intervention and control cohorts were most probably incomparable (due to the COVID‐19 pandemic).